Shelf Life Studies of Three Wasabi Flavoured Sauces - Sultana, Tamanna; Savage, GP; Porter, NG; McNeil, DL; Sedcole, JR (Bangladesh Journal of Scientific and Industrial Research, 2009)
Isothiocyanates (ITCs) contained in purees extracted from wasabi (Wasabia japonica (Miq) Matsum) can be used to manufacture a range of interesting spicy foods. In New Zealand, local manufacturers are showing interest in producing various forms of processed wasabi based sauces. However, isothiocyanates have been shown to degrade quickly in some situations. Therefore, in this study, the stability of allyl ITC was investigated in three wasabi flavoured products stored at four different temperatures (4, 10, 20 and 30°C) for 22 weeks. Two creamy (mayonnaise and tartare) sauces and a non-creamy sauce were prepared from an original recipe and flavoured with a known volume of "wasabi oil". Two types of pouches (clear and metallic plastic) were used to store each product and allyl ITC content was measured in the stored sauces at two week intervals. The initial level of allyl ITC found in mayonnaise, tartare and smoky tomato sauces were 415.3, 411.4 and 144.7 mg/ kg respectively, prior to storage. Temperature showed a strong influence in reducing allyl ITC (P=0.005 to <0.001) but no significant effect was identified for the two types of packets used. The non-creamy smoky tomato sauce was very unstable at 10°C or higher temperatures and the allyl ITC contents reduced rapidly with increasing storage temperatures. For instance, at 30°C, a 66% loss occurred by week 2 and a 90% loss occurred by week 6 in the smoky tomato sauce. However, mayonnaise and tartare sauces had a shelf life of 8 to 9 weeks with only a marginal reduction in allyl ITC (2% overall) at all the stored temperatures (4-30°C). These creamy sauces were characterized by a sudden fall in 10 weeks ending in a 69-70% loss of allyl ITC at 22 weeks. No microbial growth occurred in any of the sauces stored at any of the temperatures during the course of this storage experiment though very small change of colour was noticed for the sauces when stored at 30°C. Keywords: Bangladesh J. Sci. Ind. Res. 44(2), 147-156, 2009 DOI: 10.3329/bjsir.v44i2.3665 Bangladesh J. Sci. Ind. Res. 44(2), 147-156, 2009